2003
DOI: 10.1016/s1097-2765(03)00279-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcription within a Functional Human Centromere

Abstract: Recent data in yeast and Drosophila suggest a domain-like centromere structure with a modified chromatin core and flanking regions of heterochromatin. We have analyzed a functional human centromere and defined a region of increased chromosome scaffold/matrix attachment that overlaps three other distinct and nonoverlapping domains for constitutive centromere proteins CENP-A and CENP-H, and heterochromatin protein HP1. Transcriptional competency is intact throughout the S/MAR-enriched region and within the CENP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
158
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(168 citation statements)
references
References 35 publications
(4 reference statements)
10
158
0
Order By: Relevance
“…This is consistent with studies of the role of transcription and RNAi in centromere activity in S. pombe (Volpe et al, 2002(Volpe et al, , 2003Chen et al, 2008); however, the role for transcription in metazoan kinetochore activity has been little studied (Saffery et al, 2003;Fukagawa et al, 2004;Wong et al, 2007;Chueh et al, 2009). Our previous studies found that alphoid tetO kinetochore inactivation by the tTS correlated with the recruitment of heterochromatin protein HP1␣ and that direct recruitment of HP1␣ as a TetR:EYFP fusion protein could also inactivate the kinetochore (Nakano et al, 2008).…”
Section: Molecular Biology Of the Cell 4200supporting
confidence: 90%
“…This is consistent with studies of the role of transcription and RNAi in centromere activity in S. pombe (Volpe et al, 2002(Volpe et al, , 2003Chen et al, 2008); however, the role for transcription in metazoan kinetochore activity has been little studied (Saffery et al, 2003;Fukagawa et al, 2004;Wong et al, 2007;Chueh et al, 2009). Our previous studies found that alphoid tetO kinetochore inactivation by the tTS correlated with the recruitment of heterochromatin protein HP1␣ and that direct recruitment of HP1␣ as a TetR:EYFP fusion protein could also inactivate the kinetochore (Nakano et al, 2008).…”
Section: Molecular Biology Of the Cell 4200supporting
confidence: 90%
“…A more recent study has shown that centrochromatin has a histone modification pattern resembling that found in the downstream body of transcribed genes (Bergmann et al, 2011). Indeed, previous studies have detected transcription within rice centromeres (Nagaki et al, 2004), human neocentromeres (Saffery et al, 2003) and also within the alphoid array of a derivative of the synthetic HAC used in the present study (Iida et al, 2010). The chromatin profile at active kinetochores resembles the 'yellow' chromatin described in a recent paper (Filion et al, 2010).…”
Section: Discussionsupporting
confidence: 77%
“…While the pericentromere itself is important for providing a boundary around the centromere core, another critical region in maintaining chromosome integrity is the chromatin barrier between the pericentromere and the centromere (Saffery et al 2003;Scott et al 2007). In fission yeast, nucleosome-free tRNA act as a barrier preventing the spreading of heterochromatin into the centromere (Scott et al 2007) (Fig.…”
Section: Boundary Elementsmentioning
confidence: 99%